The loss of photosynthesis pathway and genomic locations of the lost plastid genes in a holoparasitic plant Aeginetia indica - Jingfang Chen; Runxian Yu; Jinhong Dai; Ying Liu; Renchao Zhou (BMC Plant Biology, 2020)
Abstract Background With three origins of holoparasitism, Orobanchaceae provides an ideal system to study the evolution of holoparasitic lifestyle in plants. The evolution of holoparasitism can be revealed by plastid genome degradation and coordinated changes in the nuclear genome, since holoparasitic plants lost the capability of photosynthesis. Among the three clades with holoparasitic plants in Orobanchaceae, only Clade VI has no available plastid genome sequences for holoparasitic plants. In this study, we sequenced the plastome and transcriptome of Aeginetia indica, a holoparasitic plant in Clade VI of Orobanchaceae, to study its plastome evolution and the corresponding changes in the nuclear genome as a response of the loss of photosynthetic function. Results The plastome of A. indica is reduced to 86,212 bp in size, and almost all photosynthesis-related genes were lost. Massive fragments of the lost plastid genes were transferred into the mitochondrial and/or nuclear genomes. These fragments could not be detected in its transcriptomes, suggesting that they were non-functional. Most protein coding genes in the plastome showed the signal of relaxation of purifying selection. Plastome and transcriptome analyses indicated that the photosynthesis pathway is completely lost, and that the porphyrin and chlorophyll metabolism pathway is partially retained, although chlorophyll synthesis is not possible. Conclusions Our study suggests the loss of photosynthesis-related functions in A. indica in both the nuclear and plastid genomes. The lost plastid genes are transferred into its nuclear and/or mitochondrial genomes, and exist in very small fragments with no expression and are thus non-functional. The Aeginetia indica plastome also provides a resource for comparative studies on the repeated evolution of holoparasitism in Orobanchaceae.